2022
DOI: 10.1037/sgd0000440
|View full text |Cite
|
Sign up to set email alerts
|

Monoracial and multiracial LGBTQ+ people: Comparing internalized heterosexism, perceptions of racism, and connection to LGBTQ+ communities.

Abstract: The purpose of this study was to examine the relationship between mental health outcomes, internalized heterosexism, and perceived racism on connection to the LGBTQϩ community. Responses from a diverse sample of LGBTQϩ participants of color (N ϭ 665) were gathered and analyzed. A t test revealed that the monoracial and multiracial participants did not differ in regard to internalized heterosexism, though the two racial groups differed in regard to depression. A hierarchical linear regression analysis explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…This misperception of the Black Lives Matter movement, as well as other racial justice movements, can be viewed as another manifestation of racism within LGBTQ+ communities. Research has shown the reality and impact of racism within the LGBTQ+ community (e.g., Felipe, Garrett‐Walker, & Montagno, 2020; VanDaalen & Santos, 2017), and it seems that some participants in the current study used coded racist language (e.g., aggressive, anger based) when detailing barriers to engagement in race‐based activist groups. Also unique to the literature is our finding about participants' concerns for their safety precluding them from engaging in activism.…”
Section: Discussionmentioning
confidence: 98%
“…This misperception of the Black Lives Matter movement, as well as other racial justice movements, can be viewed as another manifestation of racism within LGBTQ+ communities. Research has shown the reality and impact of racism within the LGBTQ+ community (e.g., Felipe, Garrett‐Walker, & Montagno, 2020; VanDaalen & Santos, 2017), and it seems that some participants in the current study used coded racist language (e.g., aggressive, anger based) when detailing barriers to engagement in race‐based activist groups. Also unique to the literature is our finding about participants' concerns for their safety precluding them from engaging in activism.…”
Section: Discussionmentioning
confidence: 98%
“…Part of these efforts to understand multiracial identity requires deliberate examination of ‘multiracial’ as a heterogenous group, which may be achieved by pooling years of data for statistical power. In doing so, we may be able to examine multiracial identity through an intersectional lens, to explore how multiracial mental health may be conditional on gender and sexuality (Felipe et al, 2022; Paz Galupo et al, 2019) and socioeconomic status (Bratter & Kimbro, 2013; Hitlin et al, 2006; Mitchell & Warren, 2022). Moreover, there is rich qualitative research on the lived experiences of multiracial individuals (Franco et al, 2020; Museus et al, 2015), which should be included in interdisciplinary conversations about how to advance efforts to address multiracial mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that LGBTQþ groups are instrumental for supporting identity exploration and increasing feelings of belonging on college campuses (Garvey et al, 2019;Gorman et al, 2022). However, experiences of racism within LGBTQþ communities can serve as a barrier to LGBTQþ students of color finding connections to these communities (Felipe et al, 2022).…”
Section: Support and Marginalization Within Lgbtq1 Student Groupsmentioning
confidence: 99%
“…In addition to trans-inclusive policies and practices, lesbian, gay, bisexual, trans, and queer (LGBTQ+) student groups are often valuable sources of social support for TNG students (Garvey et al, 2019). However, these groups are sometimes experienced as marginalizing and exclusionary, especially for TNG students (Marine & Nicolazzo, 2014; McKinney, 2005), students whose gender identities and/or expressions challenge the gender binary (Cruz, 2014; Goldberg & Kuvalanka, 2018; Nicolazzo, 2016b), and TNG students of color (Felipe et al, 2022). Therefore, it is also necessary to better understand if and how trans-inclusive resources may foster environments in which TNG students feel more supported within campus groups, including within LGBTQ+ clubs and organizations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation